1998
DOI: 10.1148/radiology.206.1.9423659
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt creation in children: initial clinical experience.

Abstract: This initial clinical experience suggests that TIPS creation is technically feasible and is as safe in children as in adults. TIPS creation can aid in the management of portal hypertension in children, especially in those needing temporary relief before liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 0 publications
3
40
1
Order By: Relevance
“…The literature describing results with the use of TIPS in children is scarce. Two series of 12 (5) and nine (10) patients found the procedure to be technically feasible and as safe as in adults. In pediatric patients, the potential advantages of TIPS over surgical shunts include a decreased morbidity and mortality, avoidance of surgery in the region of the hepatic hilum (which may be important in potential liver transplant candidates), and avoidance of abdominal adhesions from surgery that might prevent peritoneal dialysis if needed in the future.…”
Section: Discussionmentioning
confidence: 95%
“…The literature describing results with the use of TIPS in children is scarce. Two series of 12 (5) and nine (10) patients found the procedure to be technically feasible and as safe as in adults. In pediatric patients, the potential advantages of TIPS over surgical shunts include a decreased morbidity and mortality, avoidance of surgery in the region of the hepatic hilum (which may be important in potential liver transplant candidates), and avoidance of abdominal adhesions from surgery that might prevent peritoneal dialysis if needed in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Ciccarelli et al [7] reported a case of early portal vein thrombosis after liver transplantation treated by combining TIPS creation and thrombolysis. A series of pediatric TIPS placements included a liver transplant recipient [8]. Richard et al [5] reported a case of TIPS placement in a patient who had a liver transplant complicated by Budd-Chiari syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These sites are also amenable to embolization via shunt. TIPS have been successfully placed in infants [104,105] , and children [106][107][108] with similar efficacy.…”
Section: Emergency Transhepatic Porto-systemic Stent Shuntmentioning
confidence: 99%